Harry Potter and the Chamber of Secrets - Rowling, J. K. (London Bloomsbury, 1998)
When the Chamber of Secrets is opened again at the Hogwarts School for Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school.
Keywords: England -- Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Schools -- Potter, Harry (Fictitious character)